Integrative taxonomy of Calcarea (Porifera) from Espírito Santo, Eastern Brazil - Lopes, Matheus Vieira; Padua, André; Azevedo, Fernanda [UNESP]; Klautau, Michelle (Magnolia Press, 2025)
Despite the biogeographical and ecological importance of the Eastern Brazil ecoregion as a transitional zone, this ecoregion still represents a taxonomic and distributional gap to the knowledge on macrobenthic invertebrates. Therefore, our aim was to narrow this gap studying the calcareous sponge diversity of this important marine ecoregion. Using morphological and molecular tools, 12 species were identified, four of them new to science: Ascandra polejaeffi sp. nov., Clathrina albata sp. nov., Clathrina capixaba sp. nov., and Vosmaeropsis anomala sp. nov., with new diagnostic proposals and an amendment of the genus Vosmaeropsis. One species known from the Eastern Caribbean ecoregion and from the Fernando de Noronha and Atoll das Rocas ecoregion is being registered for the Eastern Brazil ecoregion for the first time: Clathrina delicata. Seven species previously recorded for the Eastern Brazil ecoregion were recollected in this study, corroborating their occurrence and expanding their geographic distribution within it: Borojevia brasiliensis, Borojevia trispinata, Clathrina aurea, Clathrina soluta, Grantia kempfi, Paraleucilla magna and Sycettusa hastifera. These last two species are probably invasive in Brazil and are recorded in its northernmost location in the Southwestern Atlantic. Considering the total of 43 species registered in the Eastern Brazil ecoregion, seven are shared with the Amazonia, two with São Pedro e São Paulo Islands, seven with Fernando de Noronha and Atoll das Rocas, 13 with Northeastern Brazil, one with Trindade e Martin Vaz Islands, and 14 with Southeastern Brazil ecoregion. Eastern Brazil is the best-known ecoregion in the Brazilian coast and its role as a transitional zone between tropical and subtropical faunas is discussed.
Keywords: Benthos; Biogeographical affinities; Calcaronea; Calcinea; molecular phylogeny